2014
DOI: 10.1016/j.electacta.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and Efficiency of a CuCl(aq)/HCl(aq) Electrolyzer

Abstract: The high ionic strength and complex speciation of the anolyte solution within the CuCl(aq)/HCl(aq) electrolytic cell have impeded predictions of the energy requirements for the cell's electrolytic reaction at 25 °C and 1 bar. After collecting experimental open circuit potential (OCP) data and comparing the values obtained with predictions from prospective thermodynamic models, an approach to predict thermodynamic values and the overall efficiency was formulated. The compositions of the experimental measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…An in depth analysis of the values and equations needed to describe the equilibrium potentials were published previously. 17 As can be seen from the LSV data collected, the small overpotentials needed to reach the limiting current densities suggested that the Cu II /Cu I reaction was very fast and required a very small overpotential on both Pt and GC. Furthermore, the increase in the limiting current as the rotation rate increased supported the assumption that diffusion of the active species was the source of the limiting current.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…An in depth analysis of the values and equations needed to describe the equilibrium potentials were published previously. 17 As can be seen from the LSV data collected, the small overpotentials needed to reach the limiting current densities suggested that the Cu II /Cu I reaction was very fast and required a very small overpotential on both Pt and GC. Furthermore, the increase in the limiting current as the rotation rate increased supported the assumption that diffusion of the active species was the source of the limiting current.…”
Section: Resultsmentioning
confidence: 95%
“…In solutions with high concentrations of Cl − (aq), CuCl 3 2− (aq) species had the largest concentration among Cu I complexes by about 3 orders of magnitude. 17 For this kinetic study, the next closest Cu I complex was CuCl 2 − (aq) with a bulk concentration of 10 −6 mol/kg, whereas CuCl 3 2− (aq) had a bulk concentration that was effectively 10 −3 mol/kg. The large difference in Cu I bulk concentrations in combination with the observed high current densities and limiting currents suggested that this species was a likely candidate as an electrochemically active species.…”
Section: Resultsmentioning
confidence: 99%
“…13 The nonohmic impedance contribution decreased from 4.8 to 0.27 . While it is difficult to correctly interpret the faradaic impedances as the cell reaction mechanism has not been well-established yet, 11 we have previously shown 8 that R 1 is dependent on the applied potential and related to the charge-transfer kinetics. As the anodic reaction in the cell is significantly faster than the cathode, 7 it is fair to assume that the anode kinetics are faster at 80…”
Section: Resultsmentioning
confidence: 96%
“…11 Two 85 cm 2 graphite blocks having serpentine flow channels were obtained from Electrochem Inc. and used as the end plates. 2 mol CuCl(s) dissolved in 7 mol L −1 HCl (aq), and 7 mol L −1 HCl(aq), were, respectively, fed into the anode and the cathode electrodes with a flow rate of 130 ml min −1 .…”
Section: 33mentioning
confidence: 99%
“…Canada Nuclear Laboratories (formerly Atomic Energy of Canada Limited) demonstrated hydrogen production by a CuCl electrolyzer continuously for several days and reported that electrolysis is feasible at low potentials (0.6‐0.7 V) at a current density of 0.1 A cm −2 using inexpensive materials . The Pennsylvania State University has carried out comprehensive experiments and theoretical developments on the cycle . Balashov et al performed an experimental study on a CuCl/HCl electrolyzer and reported a voltage efficiency of 80% and a current efficiency of 98%, which is with a good agreement with Faraday law.…”
Section: Introductionmentioning
confidence: 83%